(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2012)
The Syariah Court has been fraught with claims of the use of black magic or supernatural powers in the cases of marriage or divorce. The absence of legal provisions and procedures to deal with such claims often resulted being not considered. This article thus proposes Standard Operating Procedure for addressing the issues. This procedure is deemed necessary to assist all parties to uphold justice and defend the victims of spouse, if the allegations are proven true. This research was conducted through courtroom observations and interviews with judges who heard such cases and parties who claimed to have been victims of black magic. Through this Standard Operating Procedure, the truth of the allegations can be evaluated in three simple steps. First, the party claiming to have been under a spell (bewitched) he/she must prove that he/she was experiencing symptoms due to that spell. Second, the court must ask for an expert opinion to confirm that the symptoms experienced were due to witchcraft. Third, the court must issue an order compelling the victim undergo treatment if symptoms confirmed to be due to the act of black magic. Once the victim fully recovered, then the case may then be heard again. In this way, the trial will be able to be more fair and equitable. Keywords: magic, marriage and divorce, Standard Operating Procedure, syariah court